Failure to Provide Maintenance by a Husband as Grounds for Divorce: An Analysis of the Temporal Discrepancy Between Supreme Court Circular Letter (SEMA) No. 1 of 2022 and Article 116 of the Compilation of Islamic Law (KHI) - Ardi Akbar Tanjung; Kelik Wardiono; Khudzaifah Dimyati; Wardah Yuspin; Mohammed Razi Ellathodi (Mitsaqan Ghalizan, 2026)
According to both Indonesian national law and Islamic law, marriage is regarded as a sacred covenant (mitsāqan ghalīẓan) that establishes reciprocal rights and obligations between spouses, including the husband's duty to provide maintenance (nafkah). Failure to fulfill this obligation may constitute grounds for divorce, particularly through the mechanism of taklik talak violation under Article 116 of the Compilation of Islamic Law (KHI). However, Supreme Court Circular Letter (SEMA) No. 1 of 2022 introduces a different time requirement, creating a normative discrepancy with the KHI and the sighat taklik talak contained in the marriage certificate. This study examines the differences between these regulations and their implications for legal certainty, substantive justice for wives, and the practice of religious courts. This research employs a normative legal method, drawing on statutory and conceptual approaches. The findings indicate that the discrepancy in time limits creates a conflict between substantive law and judicial guidelines, resulting in inconsistent court decisions and legal uncertainty. The twelve-month requirement may disadvantage wives, particularly those in vulnerable economic conditions, by delaying access to divorce and post-divorce rights. From the perspective of substantive justice and maqāṣid al-sharī‘ah, such a prolonged period may undermine the protection of human dignity and welfare. Therefore, this study recommends harmonizing the relevant norms by maintaining the KHI as substantive law, designating SEMA as a technical guideline for evidentiary matters, and differentiating its application based on the nature of the marital violation.